The Effect of Corporate Taxpayer Compliance, the Increase of Corporate Taxpayers' Number and Tax Audits on Income Tax Receipts of Article 25 with Taxation Sanctions as a Moderating Variable in KPP Pratama Medan Petisah - Retnawati Siregar; Ilham Ramadhan Nasution; Muhammad Adil Arifin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to measure how the effect corporate taxpayer compliance, the increase of corporate taxpayers’ number and tax audits on the income tax receipts of article 25 with taxation sanctions as a moderating variable. The population of this study amounted to 12,815 business entities sourced from secondary data, if by KPP Pratama Medan Petisah from 2014-2016, the sample of this study amounted to 129 business entities selected randomly, then the number of respondents in this study were 100 business entities which were then processed using multiple linear regression and Moderated Regrression Analysis (MRA). Independent and Dependent variables were measured using the Ratio Scale and Likert Scale. The results of this study indicate that the increase of corporate taxpayers’ number has a significant effect on the income tax receipts of article 25 and compliance with corporate taxpayers and tax audit does not significantly affect the income tax receipts of article 25, but the existence of tax sanctions as a moderating variable significantly affect corporate taxpayer compliance, the increase of corporate taxpayers’ number and tax audits on the income tax receipts of article 25. This was evidenced by the increase in Adjusted R Square from 8.9% to 96.6%. And it can be ascertained that tax sanctions moderate (increase) the effect of corporate taxpayer compliance, the increase of corporate taxpayers’ number and tax audits on the income tax receipts of article 25.